EVALUASI PENGGUNAN MEDIA FUN THINKER BOOK PADA MATERI KENAMPAKAN ALAM DAN BUATAN PADA PELAJARAN IPS UNTUK SISWA KELAS V SEKOLAH DASAR - Maulana, Rindu; Aramudin, Aramudin (STKIP Persada Khatulistiwa Sintang, 2024)
The teaching and learning process is often unengaging for students and ineffective for teachers. This issue arises from various factors, such as cramped classroom conditions, students' lack of attention, minimal facilities, and a lack of engaging learning media. This study aims to evaluate the content quality and presentation of the Fun Thinkers Book and to provide improvement recommendations before dissemination. This research is an evaluation study using a formative-summative evaluation model. Evaluation is conducted through a formative evaluation stage consisting of field tests and a summative evaluation which measures the acceptance and utility of the media, resulting in various recommendations. The results indicate that the Fun Thinkers Book on temperature and heat is very suitable to be used. The content quality of the Fun Thinkers Book was rated as very good, with a score of 84% from teachers of grades 3 to 5. The presentation quality was also rated as very good, with a score of 88%. Furthermore, the assessment of student interest in the Fun Thinkers Book, involving 30 students, showed excellent results with a score of 77%. It can be concluded that the Fun Thinkers Book is highly suitable to be used, with a high level of student interest.